Causes of Deforestation and Degradation of Jhau (Casuarina equisetifolia) Plantation Along the Cox’s Bazar-Teknaf Sea Beach in Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
In this study, Jhau (Casuarina equisetifolia) plant degradation from the years 2006-2019 along the Cox’s Bazar-Teknaf sea beach has been conducted by remotely sensed satellite image analysis from the Google Earth platform. According to the research, roughly 16.39% of Jhau patches were lost between 2006 and 2010, 30.59% between 2010 and 2015, and 43.38% between 2015 and 2019. Deforestation in the Jhau forest has mostly been triggered by anthropogenic and natural factors. The anthropogenic causes that have been found in the current study region include structural development, road construction, water logging, and agricultural land expansion. Coastal erosion and new channel development are natural causes. Among the natural causes, on average, 65% of deforestation has occurred due to coastal erosion processes, and less is due to anthropogenic activities from the years 2006 to 2019. Among the locations where coastal deforestation has occurred, Charpara region and the Teknaf peninsula were found to have the most notable deforestation. The Teknaf peninsula is highly unstable, and the Jhau forest has been deforested every year due to this instability. The selection of vulnerable zones in these regions is highly needed and the selection of suitable locations for future Jhau plantations is very important to these regions.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 123-134